Fibrinogen binding to ICAM-1 promotes EGFR-dependent mucin production in human airway epithelial cells - Kim, Suil; Nadel, Jay A (American journal of physiology. Lung cellular and molecular physiology, 2009)
1 Cardiovascular Research Institute, 2 Department of Medicine, and 3 Department of Physiology, University of California, San Francisco, California Submitted 2 February 2009 ; accepted in final form 4 May 2009 Mucous hypersecretion is a serious feature of chronic airway diseases such as asthma, chronic obstructive pulmonary disease (COPD), and cystic fibrosis. Although mucins are produced via activation of an EGF receptor (EGFR) signaling cascade, the mechanisms leading to exaggerated mucin production in mucous hypersecretory diseases are unknown. Because expression of ICAM-1 and of the ICAM-1 ligand fibrinogen is increased in the airways of subjects with mucous hypersecretory diseases, we hypothesized that fibrinogen binding to ICAM-1 could increase EGFR-dependent mucin production in human airway (NCI-H292) epithelial cells. Consistent with this hypothesis, we found that an ICAM-1 neutralizing antibody and an ICAM-1(8–22) peptide that binds fibrinogen decreased mucin production induced by the EGFR ligand transforming growth factor (TGF)- dose-dependently. Exogenous fibrinogen and a fibrinogen(117–133) peptide that binds ICAM-1 rescued mucin production in cells treated with the ICAM-1(8–22) peptide. Surprisingly, the ICAM-1(8–22) peptide increased EGFR phosphotyrosine and phospho-ERK1/2 in cells treated with TGF- . The ICAM-1(8–22) peptide-induced increases in EGFR phosphotyrosine and phospho-ERK1/2 were prevented by exogenous fibrinogen, by the fibrinogen(117–133) peptide, and by selective inhibitors of phospholipase C (PLC), protein kinase C (PKC)- /β, and metalloproteases. These results suggest that fibrinogen binding to ICAM-1 promotes mucin production by decreasing TGF- -induced EGFR and ERK1/2 activation and that the fibrinogen-ICAM-1-dependent decrease in EGFR and ERK1/2 activation occurs via inhibition of an early positive feedback pathway involving PLC- and PKC- /β-dependent metalloprotease activation and subsequent metalloprotease-dependent EGFR reactivation. cell surface molecules; innate immunity; mucous hypersecretion; cell differentiation Address for reprint requests and other correspondence: S. Kim, Cardiovascular Research Inst., Univ. of California San Francisco, Box 0130, San Francisco, CA 94143-0130 (e-mail: suil.kimatucsf.edu )